Effects of extracellular DNA on dual-species biofilm formed by Streptococcus mutans and Candida albicans. (May 2021) - Guo, Haoran; Chen, Yitong; Guo, Wenjin; Chen, Jingyu
Abstract: Streptococcus mutans is the most important acid-producing pathogen that causes dental caries, while Candida albicans is an opportunistic fungal pathogen that is frequently detected in conjunction with heavy infection by S. mutans . Their interactions in dental plaque biofilms remain unclear. Extracellular DNA (eDNA) is found in oral biofilms, but its effects have not been thoroughly defined. In this study, the role of eDNA in dual-species biofilms formed by S. mutans and C. albicans was investigated. With eDNA removal, the growth of both strains was not affected, but the formation of dual-species biofilms obviously decreased. In addition, the removal of eDNA spatially disrupted the structure of the dual-species biofilm. It was also shown that eDNA mainly affected the initial attachment and development stages of the dual-species biofilms but not the well-developed biofilms. A similar phenomenon was also observed in the cell viability of dual-species biofilms after DNase I treatment. To further exploration, we analyzed the expression of genes associated with biofilm formation in both S. mutans and C. albicans . We determined that the co-cultivation of S. mutans and C. albicans promotes the expression of genes related to extracellular polysaccharide production (e.g., gtfC ), adhesion (e.g., spaP, epa1 ), mycelial transformation (e.g., hwp1 ), and drug resistance (e.g., cdr2 ). However, these genes were significantly downregulated when the eDNA of the dual-species biofilm was removed by adding DNase I compared to those untreated groups. Altogether, eDNA removal, such as that by DNase I treatment, could be considered a promising strategy to control oral biofilms and biofilm-associated oral diseases. Highlights: Extracellular DNA (eDNA) removal conferred a decrease on dual-species biofilm formation formed by  Streptococcus mutans  and  Candida albicans . The decrease of dual-species biofilm formation by eDNA removal was mainly caused by disrupting the integrity of the biofilm structure. The eDNA removal had significant inhibitory effects on biofilm formation and cell viability during the initial attachment and developing stage of the dual-species biofilm formation, but little effect on well-developed biofilm. With transcription analysis, it revealed that eDNA performed its multiple functions by affecting the expression of genes related to dual-species biofilm formation.